APPLICATION OF SEMIOTICS IN ORGANIZATIONAL COMMUNICATION - Rasakumaran, A. (University of Jaffna, 2018)
This article presents the brand management process based on the Peircean principles of Semiotics, for sign analysis. Based on the application of semiotics for brand management, it is argued that consumers are able to receive a brand that allows the appropriation of information that leads them to build knowledge and, therefore, make purchasing decisions. Bibliographical survey and theoretical discussion were employed as the research method. Results reveal that the application of semiotics theory reduces the differences between the brand identity communicated by the organization and the brand image perceived by customers or consumers. As this study is theoretical, neither direct description of empirical object nor an experimental process being offered may be a limitation.
Keywords: Semiotics; Organizational communication; Information flows; Brand management